ANALISIS AVAILIBILITYKINERJA BOILER PADA PT. ROHUL SAWIT INDAH - Fahrizal - (Universitas Pasir Pengaraian, 2014)
To support optimal results in the processing of palm fruits into palm oil (crude palm oil), the conditionsin the boiler must be properly maintained and operated properly, so that the process of production activity isnot impaired. In boiler operations often suffer disturbance, damage in minor life, namely the outbreak ofsuperheater pipes, it is very disturbing production activities.This study aimed to calculate the performance Availabilityoperated boiler in order to reduce thephysical components are not damaged during normal operation and case unplanned maintenance activities.It is very important in order to achieve a more efficient and economical operation of the plant andequipment.